2020
DOI: 10.3390/ijerph17155602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Deoxynivalenol in Wheat, Corn and Its Products and Estimation of Dietary Intake

Abstract: The main goal of the present research was to explore the seasonal variation of deoxynivalenol (DON) in wheat, corn, and their products, collected during 2018–2019. Samples of 449 of wheat and products and 270 samples of corn and their products were examined using reverse-phase liquid chromatography with a UV detector. The findings of the present work showed that 104 (44.8%) samples of wheat and products from the summer season, and 91 (41.9%) samples from winter season were contaminated with DON (concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
1
21
0
2
Order By: Relevance
“…Mycotoxins are secondary metabolites produced during pre- and postharvest conditions. Mycotoxins are highly diversified, with about 450 different structural categories already identified and classified [ 7 , 8 , 9 ]. The most important mycotoxins found as food contaminants include aflatoxins, ochratoxin A, fumonisins, zearalenone, trichothecenes, and patulin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites produced during pre- and postharvest conditions. Mycotoxins are highly diversified, with about 450 different structural categories already identified and classified [ 7 , 8 , 9 ]. The most important mycotoxins found as food contaminants include aflatoxins, ochratoxin A, fumonisins, zearalenone, trichothecenes, and patulin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the LOD and LOQ were 25 and 50 µg/kg, respectively. In another study [10], good recoveries of DON were observed in wheat and corn products with levels ranged from 80.8 to 92.6%, RSD ranged from 9 to 27%. However, the LOD and LOQ values were slightly higher, i.e., 50 and 100 µg/kg, respectively, as compared to the present study.…”
Section: Percentage Recoveries = (µ )mentioning
confidence: 89%
“…The trichothecenes family's an important class and closely linked to vomitoxin is deoxynivalenol (DON) mycotoxin, and it is mainly produced by Fusarium species, especially F. graminearum and F. culmorum, [6][7][8][9][10]. The DON is also known to produce similar forms of other toxins, recognized as masked mycotoxins, which usually remain undetected during the analytical process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus fungi would be able to produce AFB 1 within this temperature range (maximum mycotoxin production temperature 40 • C), however the temperature is not suitable for the growth of Fusarium fungi (maximum mycotoxin production temperature 30 • C), which produces DON [46,47]. High levels of DON have been detected in wheat and corn products from the same studied region in a recent study [18]. More than 40% of samples were tested and found to be contaminated by DON with an average contamination level of 1000 µg/kg, which is close to the EU regulatory limit of 1250 µg/kg.…”
Section: Exposure Levels Of Don and Afbmentioning
confidence: 99%
“…In Pakistan, evidence of DON contamination in food has been reported, but data are limited [15][16][17]. A recent study showed high levels of DON in 449 wheat and 270 corn samples collected from the studied area (more than 40% with mean level around 1000 µg/kg) [18].…”
Section: Introductionmentioning
confidence: 99%